2017
DOI: 10.1007/s00586-017-4974-1
|View full text |Cite
|
Sign up to set email alerts
|

A histomorphometric study of the cancellous spinal process bone in adolescent idiopathic scoliosis

Abstract: Bone histomorphometry indicated that bone fragility and abnormal bone turnover were common in AIS patients. These abnormalities might contribute to the poor bone status and etiology in AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Because osteocytes are embedded in a mineralized matrix, the interconnecting network is characterized as lacuno-canalicular network (LCN), which is important for mechanosensation and mechanotransduction (17). Previous bone biopsy histomorphometry studies revealed lower bone mineralization, a greater osteoblast number, and a lower number of osteocytes in patients with AIS and with severe spinal deformity (18,19), suggesting the likelihood of impaired osteoblasts to osteocytes differentiation. Recently, our cellular study first reported defective osteocyte activities and lower expression of dendritic markers in AIS owing to overexpression of miRNA-145 (20).…”
mentioning
confidence: 99%
“…Because osteocytes are embedded in a mineralized matrix, the interconnecting network is characterized as lacuno-canalicular network (LCN), which is important for mechanosensation and mechanotransduction (17). Previous bone biopsy histomorphometry studies revealed lower bone mineralization, a greater osteoblast number, and a lower number of osteocytes in patients with AIS and with severe spinal deformity (18,19), suggesting the likelihood of impaired osteoblasts to osteocytes differentiation. Recently, our cellular study first reported defective osteocyte activities and lower expression of dendritic markers in AIS owing to overexpression of miRNA-145 (20).…”
mentioning
confidence: 99%
“…In a previous study, a significant difference in the bone mineral density between patients with AIS and non-affected paired controls was proven ( 32 ). Li et al reported that AIS patients had poorer bone mineral density of the bilateral femoral neck than controls ( 13 ), and lower bone volume from the histological sections of the spinous process taken from AIS patients was found ( 33 ). Besides, Almomen et al reported that female AIS patients with greater higher Cobb angles exhibited a significantly higher risk of low bone density ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that 59% of human patients with AIS had higher serum level of TRAP5b than humans without AIS (> +1.88 SD), suggesting higher rates of bone resorption are common in AIS patients [ 9 ]. Additionally, in another study, we presented a detailed histomorphometric analysis of cancellous spinal process bone in AIS, and indicated that 76% of human patients with AIS had high turnover and that biomarkers of bone turnover may provide a noninvasive means for classifying AIS into specific metabolic types [ 50 ]. Taken together, we consider that bisphosphonate therapy should be preferentially adapted for treating high-turnover AIS patients before the growth of severe scoliosis is complete (i.e.…”
Section: Discussionmentioning
confidence: 99%